Florentino Pérez Embid (1918-1974), una vida de trabajo entre la universidad y la política / Florentino Pérez Embid (1918-1974), a life of work between university and politics - Onésimo Díaz Hernández (Studia et Documenta, 2025)
This article will show how Florentino Pérez Embid’s professional activity reflected the message of the sanctification of work preached by José María Escrivá de Balaguer. In his youth, Pérez Embid wanted to become a professor, which he achieved in 1949. Shortly afterwards, he entered political life when he accepted the post of Director General of Propaganda in 1951. As well as being very active in the university and political sectors, he was responsible for formative activities in Opus Dei.